Alright,
directix is y=something so it opens down or up
we use
(x-h)²=4p(y-k)
the vertex is (h,k)
and p is distance from focus to vertex
if focus is above directix, p is positive
if focus is below directix, p is negative
so we gts
focus=(1,1)
directix is y=-1
1>-1
focus is above
oh, vertex is in middle of focus and directix
so
beteeen (1,1) and y=-1 is, hmm
that is a distance of 2 vertically
2/2=1
1 down from (1,1) is (1,0)
vertex is (1,0)
p=1
so
(x-1)²=4(1)(y-0)
solving for y to get into f(x)=something form
(x-1)²=4y
y=1/4(x-1)²
f(x)=1/4(x-1)²
4th option
Answer 6 is and exponential, but I don’t know what 7 is, sorry
Answer:
16
Step-by-step explanation:
if c = 4, then
(c)(c) = 16
if I misinterpreted your equation, please tell me.
Answer:
Step-by-step explanation:
6x + 3y = -18
Taking 3 common from left side
so, 3(2x+y) = -18
2x+y = -18/3
2x+y = -6 (equation 1)
and, 7x + 7y = 0
Taking 7 as commom from left side
7(x + y) = 0
x + y = 0/7
x + y = 0 (equation 2)
now , by using elimination method
subtracting equation2 from equation1
2x + y - (x + y)= -6 - 0
2x + y - x - y = -6
x = -6
so, x = -6
substituting value of x in equation 1
2(-6) + y = -6
-12 + y = -6
y = -6 +12
y = 6
hence, the value of x = -6
and value of y = 6
To solve this equation, all you need to do is substitute the value of x that would be like this y = -2 (-3) -7 and solve, the answer would be -1.